MAGNETITE COMPOSITIONS AND OXYGEN FUGACITIES OF THE KHIBINA MAGMATIC SYSTEM - Ryabchikov I.D.; Kogarko L.N. (My University, 2006)
Most titanomagnetite in the Khibina alkaline igneous complex, sampled through 500 m of a vertical cross-section, is represented by Ti-rich varieties. The ulvöspinel component is most commonly around 55 mol%, rarely reaching up to 80 mol%. We calculated an fO2-T diagram for magnetite + ilmenite + titanite + clinopyroxene + nepheline + alkali feldspar and magnetite + titanite+ clinopyroxene + nepheline + alkali feldspar phase assemblages at a hedenbergite activity of 0.2. The diagram shows that magnetites with 55 mol% of ulvöspinel crystallized at oxygen fugacities just slightly below the quartz-fayalite-magnetite buffer. More Ti-rich varieties crystallized at higher temperatures and slightly lower ΔQMF values, whereas more Ti-poor magnetites crystallized at or below about 650 °C. Under the redox conditions estimated for the apatite-bearing intrusion of the Khibina complex (close to the QFM buffer), substantial quantities of methane may only form during cooling below 400 °C in equilibrium with magma. However, even at higher orthomagmatic temperatures and redox conditions corresponding to ΔQMF = 0, the hydrogen content in the early magmatic stage is not negligible. This hydrogen present in the gas phase at magmatic temperatures may migrate to colder parts of a solidifying magma chamber and trigger Fischer-Tropsch-type reactions there. We propose therefore, that methane in peralkaline systems may form in three distinct stages: orthomagmatic and late-magmatic in equilibrium with a melt and - due to Fischer-Tropsch-type reactions - post-magmatic in equilibrium with a local mineral assemblage. © 2006 Elsevier B.V. All rights reserved.
Keywords: ALKALINE MAGMAS; FE-TI OXIDES; HYDROCARBONS; KHIBINA COMPLEX; OXYGEN FUGACITY; TITANITE